Japan : - Gibney, Frank (Norton, 1975)
"What is the secret of Japan's economic success? What are the country's prospects for the future? Japan: The Fragile Superpower sets out to answer these intriguing questions and at the same time provides a penetrating analysis of the inner dynamics of Japanese business, politics, and culture." Frank Gibney's widely acclaimed book was long required reading for anyone interested in modern Japan. Nearly twenty years later, many of Gibney's original observations still hold true.